1988
DOI: 10.1111/j.1365-2222.1988.tb02910.x
|View full text |Cite
|
Sign up to set email alerts
|

The major aeroallergens in Guangxi, China

Abstract: Summary Over a 2‐year period we have identified pollen grains from 48 families of grasses, as well as mould spores and mite particles during air sampling in Guangxi Province. The major aeroallergens were Artemisia, Moraceae and Euophoribiacea, and the spores of Aspergillus, Penicillinum, Cephalosporium and Helminthosporium. Mites were probably also one of the major outdoor aeroallergens. Our investigations also included inspection of the vegetation of the geographical area involved, as well as skin testing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Guangxi Zhuang Autonomous Region, inhabited by the Du’an goat, is in the south subtropical zone, where the average annual temperature is 17–23 Celsius degree, the average maximum temperature is about 29 Celsius degree in July [ 41 ]. In the genome-wide screen, we found a very strong selective signal with a high-frequent nonsynonymous SNPs in MTOR (c.G5507C:p.G1836A).…”
Section: Discussionmentioning
confidence: 99%
“…Guangxi Zhuang Autonomous Region, inhabited by the Du’an goat, is in the south subtropical zone, where the average annual temperature is 17–23 Celsius degree, the average maximum temperature is about 29 Celsius degree in July [ 41 ]. In the genome-wide screen, we found a very strong selective signal with a high-frequent nonsynonymous SNPs in MTOR (c.G5507C:p.G1836A).…”
Section: Discussionmentioning
confidence: 99%
“…The most important being Japanese cedar followed by pine [73, 74]. Artemisia , Casuarinaceae, Euphorbiaceae, Graminae, Moraceae and Pinaceae are the major contributors to the atmosphere of China [75]. Chen and Huang [76] observed that in Taiwan the tree species contribute 56 percent of the total pollen count.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that there is different immunogenicity between dust mites and other allergens such as mugwort pollen. Mugwort is one of the most common pollen allergens in China (30,31). Allergic immune responses to the major mugwort pollen allergen Art, which belongs to the pectate lyase allergen family, are characterized by IgE binding and T-cell proliferation (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%